Ukraine : Technical Assistance Report-Reducing Social Security Contributions and Improving the Corporate and Small Business Tax System. (IMF Staff Country Reports; Country Report ;, 2016)
Social Security Contributions (SSC) in Ukraine need urgent attention. If nothing is done, the budget is poised to lose 4.5 percent of GDP in revenues in 2016 due to a legally mandated SSC rate reduction adopted in March 2015. The Ministry of Finance (MoF) is studying a number of options to find a responsible, revenue neutral, approach to lowering SSC rates, which at 40 percent of payroll are above all countries in the OECD. At the same time, Ukraine hosts a very large informal sector which stands as a difficult obstacle to developing its social and economic potential. However, there is no fiscal space to forgo tax revenues. The shift of the tax burden away from labor (as recommended by previous FAD missions) cannot jeopardize the integrity of public finances; it needs compensation from reliable sources of tax revenues. A closely connected issue is the Single Tax System (STS) originally designed for small entrepreneurs, but which has become very porous to others. The regime allows qualifying taxpayers to pay a very low tax on income and a symbolic SSC fee, and offers ample opportunities for avoidance by employers who contract their workers as independent entrepreneurs. To restore horizontal equity with regular employees, the STS requires fundamental reform, addressing: a (turnover) cap for the STS that is too high, a system that effectively overrides the VAT threshold, unnecessarily admits legal persons and offers important tax and SSC incentives for employees to reclassify as independent entrepreneurs - a practice that is currently very difficult to combat due to poor rules and enforcement practices. However, the revenue potential here should not be exaggerated given the difficulty in taxing this segment of the population.